(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Using protective equipment in medical activities is a very urgent requirement. Protective means in addition to the function of protecting health workers during professional practice also have a particularly important position to ensure patient safety. Objectives: Describe the knowledge and practice on using personal protective equipment of medical staff at the National Eye Hospital and analyze some related factors. Methods: Cross-sectional survey, quantitative research. Results: The rate of health workers with knowledge on using personal protective equipment reached 71,2%. The rate of health workers with practices on using personal protective equipment reached over 80%. There are 4 factors related to knowledge on using personal protective equipment including: age, working position, working time and professional qualifications. Three factors related to practices on using personal protective equipment including: Gender, working position and time of training on infection control (p<0.05).